(untitled) (Uzbek Scholar Journal, 2022)
The article discusses the technology of improving reading skills, the culture of receiving information on social phenomena used in terms such as "reading culture", "reading culture", "reading culture", as well as the formation of reading culture in primary school students. opinions were expressed.